Age trends in musical preferences in adulthood: 1. Conceptualization and empirical investigation. (December 2017) - Bonneville-Roussy, Arielle; Stillwell, David; Kosinski, Michal; Rust, John
This article aims to fill some gaps in theory and research on age trends in musical preferences in adulthood by presenting a conceptual model that describes three classes of determinants that can affect those trends. The Music Preferences in Adulthood Model (MPAM) posits that some psychological determinants that are extrinsic to the music (individual differences and social influences), and some that are intrinsic to the music (the perceived inner properties of the music), affect age differences in musical preferences in adulthood. We first present the MPAM, which aims to explain age trends in musical preferences in adulthood, and to identify which variables may be the most important determinants of those trends. We then validate a new test of musical preferences that assesses musical genres and clips in parallel. Finally, with a sample of 4, 002 adults, we examine age trends in musical preferences for genres and clips, using our newly developed test. Our results confirm the presence of robust age trends in musical preferences, and provide a basis for the investigation of the extrinsic and intrinsic psychological determinants of musical preferences, in line with the MPAM framework.